PERAN WORK LIFE BALANCE MEMEDIASI BEBAN KERJA TERHADAP STRES KERJA KARYAWAN BANK BRI GATSU DENPASAR - Cahyathi, I Gusti Ayu Widya Ari; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to analyze the role of work life balance in mediating the effect of workload on employee work stress at Bank BRI Gatot Subroto Denpasar Branch. This study used a sample of 54 employees. The method used in this study is a survey method with questionnaire and interview techniques with PLS-based inferential statistical analysis tools Structural Equation Modeling (SEM). The results showed that workload had a significant positive effect on work stress. Workload has a significant negative effect on work life balance, work life balance has a significant negative effect on work stress, and work life balance mediates the effect of workload on work stress. The implication of this research is to prove social exchange theory and homeostatic theory and their relation to research variables. This research also offers the benefits of work life balance, workload management against work stress. work life balance; workload ; work stress;